2017
DOI: 10.3892/etm.2017.4200
|View full text |Cite
|
Sign up to set email alerts
|

(+)-Cholesten-3-one induces osteogenic differentiation of bone marrow mesenchymal stem cells by activating vitamin D receptor

Abstract: In our previous reports, it was revealed that steroids in traditional Chinese medicine (TCM) have the therapeutic potential to treat bone disease. In the present study, an in vitro model of a vitamin D receptor response element (VDRE) reporter gene assay in mesenchymal stem cells (MSCs) was used to identify steroids that enhanced osteogenic differentiation of MSCs. (+)-cholesten-3-one (CN), which possesses a ketone group that is modified in cholesterol and cholesterol myristate, effectively promoted the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Understanding the molecular mechanisms underlying MSC osteogenic differentiation is important for therapeutic purposes. Our previous reports [ 5 , 6 ] indicated that CN has the potential to promote the osteogenic differentiation of MSCs. However, the role of epigenetic regulation in the CN-induced osteogenic differentiation of MSCs remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Understanding the molecular mechanisms underlying MSC osteogenic differentiation is important for therapeutic purposes. Our previous reports [ 5 , 6 ] indicated that CN has the potential to promote the osteogenic differentiation of MSCs. However, the role of epigenetic regulation in the CN-induced osteogenic differentiation of MSCs remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analysis of the miRNA-mRNA-lncRNA interaction network identified 16 core genes, including 6 mRNAs (Vdr, Mgp, Fabp3, Fst, Cd38, and Col1a1), 5 miRNAs (miR-483, miR-298, miR-361, miR-92b and miR-155), and 5 lncRNAs (NR_046246.1, NR_046239.1, XR_086062.1, XR_145872.1 and XR_146737.1). Vdr, a ligand-activated transcription factor, has been reported to be a core gene during MSC osteogenic differentiation [ 5 , 6 , 50 ], and matrix gla protein (Mgp) has been recognized as a potent calcification inhibitor and regulator of bone morphogenetic protein-2 (BMP-2) [ 51 ]. Wang et al [ 52 ] indicated that overexpression of fatty acid binding protein 3 (Fabp3) inhibited MSC growth and proliferation via negatively regulating the cell cycle and MSC growth factors and enhancing cell survival under hypoxic or ischaemic conditions, which indicated that the Fabp3 gene potentially promotes MSC osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations